1995
DOI: 10.1111/j.1471-0528.1995.tb09027.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of cervical intraepithelial neoplasia among women with renal transplant in relation to cyclosporine

Abstract: Objective To evaluate the policy of an annual smear to screen renal transplant recipients for cervical intraepithelial neoplasia and invasive carcinoma and to determine the incidence of abnormal smears and CIN before and after the introduction of cyclosporine (1983). Design A retrospective study over the period 1971 to 1992. Subjects Postmenarchial women who received renal transplants and who were on immuno‐suppressive treatment for at least one month. Mean outcome measures Cytology and histology results. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…There is some debate whether immunosuppressed patients should be screened more frequently, and in some European centres annual cytology combined with colposcopy is recommended 139 . Data from the renal transplant population (receiving multiple immunosuppressive agents) suggests a fivefold increase in the prevalence of abnormal cervical cytology (15%) above the normal population 140 . However, there is no information on risk in dermatology patients on single immunosuppressant drugs such as azathioprine.…”
Section: 5 Other Baseline Considerationsmentioning
confidence: 99%
“…There is some debate whether immunosuppressed patients should be screened more frequently, and in some European centres annual cytology combined with colposcopy is recommended 139 . Data from the renal transplant population (receiving multiple immunosuppressive agents) suggests a fivefold increase in the prevalence of abnormal cervical cytology (15%) above the normal population 140 . However, there is no information on risk in dermatology patients on single immunosuppressant drugs such as azathioprine.…”
Section: 5 Other Baseline Considerationsmentioning
confidence: 99%
“…A retrospective study described the cervical screening of 144 transplant recipients; the overall incidence of abnormal cytology was 17.3%, and histopathology identified 6.9% of CIN I and CIN II, and 2.1% of CIN III [13]. Moreover, a nationwide populationbased retrospective cohort study set up in Australia showed that standardized incidence ratios for cancers associated with human papillomavirus infection, notably anogenital cancers (RR = 5.96; CI95% 3.93-8.67), were significantly elevated during transplant function, but not during dialysis [15].…”
Section: Commentmentioning
confidence: 99%
“…This may, however, increase the incidence of diseases associated with human papillomavirus infection, such as cervical intraepithelial neoplasia and cervical cancer [13][14][15]. Systematic annual cervical screening should therefore be advised.…”
mentioning
confidence: 95%
“…It is known that LSILs are related to low risk HPV types 6, 11, 40, 42, 43, 44, 54, 61, 70, 72, 81 and HSILs and cervical cancers are related to high risk HPV types 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 68, 73 and 82. But some cervical intraepithelial neoplasia 2 (CIN 2) and 3 lesions develop without a preexisting CIN 1 [5,6]. And HPVs are positive in CIN 1 about 85% [7,8].…”
mentioning
confidence: 99%
“…And HPVs are positive in CIN 1 about 85% [7,8]. Some CIN 1s and almost all CIN 2 and 3 lesions are associated with monoclonal "high-risk" HPV types [5,9]. For clinical convenience, cytological LSIL should be proven as pathological LSIL and cytological HSIL should be proven as pathological HSIL.…”
mentioning
confidence: 99%